Author Correction: An Autogenously Regulated Expression System for Gene Therapeutic Ocular Applications. Issue 1 (December 2018) - Sochor, Matthew; Vasireddy, Vidyullatha; Drivas, Theodore; Wojno, Adam; Duong, Thu; Shpylchak, Ivan; Bennicelli, Jeannette; Chung, Daniel; Bennett, Jean; Lewis, Mitchell
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.